2018
DOI: 10.4103/jnrp.jnrp_8_18
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Amyotrophic Lateral Sclerosis in Natives of Western Himalayas: Hospital-Based Cohort Study

Abstract: Background:Despite the disabling nature of amyotrophic lateral sclerosis (ALS), there are no contemporary data on clinical characteristics available from rural hilly states from India. Thus, the present study aimed at reporting clinical profile in ALS patients from natives of Western Himalayas.Materials and Methods:A total of 32 patients of ALS were enrolled over a period of 1 year (2013–2014) in the present study. The demographic profile, clinical characteristics, and risk factors were systematically recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…This observation might be explained by the lower progression rate of disease in our ALS patients in comparison to previous studies where CSF toxicity was shown [ 17 , 23 ]. The disease pattern in India has been described as a slow progressing disease in comparison to western counterparts in various studies [ 25 , 26 ]. Galán et al observed that CSF toxicity was patient-specific and not all patients’ CSF was toxic.…”
Section: Discussionmentioning
confidence: 99%
“…This observation might be explained by the lower progression rate of disease in our ALS patients in comparison to previous studies where CSF toxicity was shown [ 17 , 23 ]. The disease pattern in India has been described as a slow progressing disease in comparison to western counterparts in various studies [ 25 , 26 ]. Galán et al observed that CSF toxicity was patient-specific and not all patients’ CSF was toxic.…”
Section: Discussionmentioning
confidence: 99%
“…(Table . 1) Bulbar onset is more common in elderly (age >60 years) females and females have worse prognosis than males. 7 25% of patients with ALS have the bulbar onset. 9…”
Section: Discussionmentioning
confidence: 99%